2019
DOI: 10.1055/s-0039-1684043
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Toxicity: Causes, Evaluation Protocols, Intervention, and Management

Abstract: The loss of vestibular function, typically bilateral, due to chemical solvents and pharmacological agents is not rare and has been investigated and reported for many years. The successful treatment of bacterial infections and sepsis with IV antibiotics and cancer-fighting drugs like cisplatin makes the decision to use these life-saving drugs less of a debate, despite their potential deleterious effect on balance and equilibrium. The purpose of this article is to provide the reader with an overview of the more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Bilateral vestibulopathy and disequilibrium is reported in the literature secondary to chemotherapy. 10 Medical history is remarkable for hypertension and acquired Deafness due to spinal meningitis at 2.5 years of age, post language acquisition. Lightheadedness, dizziness, vertigo, and orthopedic concerns were all denied during the history and intake portion of the evaluation.…”
Section: Case Description Historymentioning
confidence: 99%
“…Bilateral vestibulopathy and disequilibrium is reported in the literature secondary to chemotherapy. 10 Medical history is remarkable for hypertension and acquired Deafness due to spinal meningitis at 2.5 years of age, post language acquisition. Lightheadedness, dizziness, vertigo, and orthopedic concerns were all denied during the history and intake portion of the evaluation.…”
Section: Case Description Historymentioning
confidence: 99%
“…As intracellular energy levels and mitochondrial function are rapidly compromised in necrosis and not in apoptosis, ATP levels in our model were quantified to determine cell death fate (Tsujimoto, 1997). The model was then used to assess the adverse effect of styrene, a widely-used aromatic solvent with known cochleotoxic properties (Campo et al, 2001;Fetoni et al, 2021Fetoni et al, , 2016Sliwinska-Kowalska et al, 2020) and deleterious effects on the sensory-motor integration of vestibular pathways (Calabrese et al, 1996;Gans et al, 2019;Larsby et al, 1978;Möller et al, 1990;Niklasson et al, 1993;Odkvist et al, 1982;Tham et al, 1982;Zamyslowska-Szmytke and Sliwinska-Kowalska, 2011) which has a demonstrated toxic effect on utricular explants (Tallandier et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, the precise mechanism through which aromatic solvents affect the vestibular system remains elusive. Thus, we still do not know whether the solvents affect the brain structures regulating balance or the vestibular labyrinth localized in the inner ear (Gans et al, 2019).…”
Section: Introductionmentioning
confidence: 99%